1976
DOI: 10.1111/j.1365-2621.1976.tb00764.x
|View full text |Cite
|
Sign up to set email alerts
|

A method for measuring tomato fruit firmness using a modified shear press

Abstract: SummaryTomato fruit firmness was measured with a modified shear press by compressing individual fruit by 5 mm between two flat surfaces. The system was calibrated with a spring balance and the relationship between applied force and proving ring deformation was linear over the range tested.The correlation coefficient between tomato fruit firmness as measured by a finger feel panel and the shear press was 0·988. Minimum shear press firmness values for acceptability of fruit for sale at retail level and use in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Ripening leads to a significant decrease in bioyield, toughness and fruit firmness and an increase in compliance. These findings confirm the reports of previous workers (Adegoroye, 1980;Gormley & Keppel, 1976;Hall, 1964;Holt, 1970). The effect of ripening on deformation was not significant while compliance appeared as the most useful parameter for detecting changes in the softness of tomato fruits.…”
Section: Effect Of Maturity On Force-deformation Characteristicssupporting
confidence: 93%
“…Ripening leads to a significant decrease in bioyield, toughness and fruit firmness and an increase in compliance. These findings confirm the reports of previous workers (Adegoroye, 1980;Gormley & Keppel, 1976;Hall, 1964;Holt, 1970). The effect of ripening on deformation was not significant while compliance appeared as the most useful parameter for detecting changes in the softness of tomato fruits.…”
Section: Effect Of Maturity On Force-deformation Characteristicssupporting
confidence: 93%
“…capable of being sliced ea. 'ily, is about 540 g. Results for 19 batches of tomatoes tested have shown that only 80% of fruit in a 12 lb box was within ± 20% of the mean firmness value for the batch, 9 thus indicating large differences in the firmness of fruit within each batch. If, therefore, a lot of tomatoes has a mean firmness of 680 g force there would be individual fruit with values much lower than this.…”
Section: Interpretation Of Firmness Valuesmentioning
confidence: 99%
“…On the basis of panel tests 9 it was found that the minimum firmness value at which an individual tomato fruit could be acceptable for sale at retail level is about 680 g force, while the value for use in the home, i.e. capable of being sliced ea.…”
Section: Interpretation Of Firmness Valuesmentioning
confidence: 99%
“…A set of 20 tomatoes a day, randomly selected from the initial group, was used as recommended by Gormley & Keppel (1976) and presented to the nine previously selected judges. Each judge carried out an individual evaluation of the samples, checking his perception on the scale as explained before.…”
Section: Sensory Analysis For Colormentioning
confidence: 99%